Assessing the utility of the national student financial aid scheme towards skills development: A case of a rural university in South Africa - Mokgotho, M. G.; Njoko, M. B.; Burman, C. J. (South African Journal of Higher Education, 2023)
The National Student Financial Aid Scheme (NSFAS) was introduced in 1999 in South Africa to provide financial support for disadvantaged students through the provision of both loans and bursaries. This article reflects on the effects of the scheme on skills development within two faculties at the University of Limpopo. The research was undertaken in 2021 employing an exploratory qualitative methodology. A total of eighteen participants were purposively selected from two of the four faculties of the University of Limpopo. A semi-structured interview guide was utilised to elicit narrative data from all participating beneficiaries of the NSFAS. The narrative data were analysed using a thematic coding design and interpretations of the findings were subsequently made. The interpretation of the analysis focused on the effect of the NSFAS support on students’ skills development. The findings suggest that NSFAS funding contributed to the development of soft skills of beneficiaries which included financial security; spending prioritisation and collaborative budgeting; time-management skills; self-esteem and skills development opportunities. Whilst the findings are localised, they do suggest that further research could be undertaken into the potentials of NSFAS to boost students’ soft skills development during their time within a higher education institution.